Hemodialysis catheter related blood stream infections - Subramanyam, Tanuja Nambakam; P. Vakrani, Girish (International Journal of Research in Medical Sciences, 2018)
Background: Hemodialysis catheter related blood stream infection (CRBSI) is common cause for sepsis in hemodialysis patients with high morbidity and mortality. It has to be diagnosed promptly for early treatment to avoid serious complications including catheter removal. This prospective study was undertaken to study clinical features, to validate use of cultures drawn from different sites for diagnosis and management of hemodialysis catheter related blood stream infection (CRBSI). As there is paucity of data regarding CRBSI, hence the study was undertaken. Methods: All hemodialysis patients with CRBSI between October 2016 to October 2017 were included. Variables like different catheter position, blood cultures collected from peripheral vein, both catheter hubs, catheter exit site swab, and catheter tip cultures were analyzed with respect to time to culture positivity, microbes and its management were analyzed. Results: Mean duration of hemodialysis catheter inside patient was 24days, most common risk factor for CRBSI was diabetes mellitus (58%) followed by surgery (50%), previous dialysis catheterization within preceding 2months (33%). 30% patients had history of guide wire exchange of catheters previously, most had temporary catheter (88%), most common site of catheter was right internal jugular vein (58%). Cultures showed gram positive organisms in 63%. It was found that same monomicrobial growth was noted in most cultures stating less chances of contamination. Exit site, catheter tip samples and blood sample from catheter’s venous hub yielded early result. It was found that same monomicrobial growth was noted in most cultures stating less chances of contamination. Among complications, 8% had endocarditis, 61% had catheter removal. Average hospital stay was 9days. Deferve scence was noted upon antibiotic therapy and catheter removal in most cases. Death was noted in 8% due to sepsis. Conclusions: CRBSI are major cause of admissions, morbidity and mortality in hemodialysis patients on catheters. Gram positive organisms were commonest pathogens causing CRBSI. Exit site, catheter tip samples and blood sample from catheter’s venous hub yielded early result. Peripheral blood sampling for culture diagnosing was unnecessary. Most requires 2-6weeks systemic antibiotics and catheter removal especially if persistent fever and systemic complications are present.